Pelatihan Pembuatan Minuman Kesehatan Berbahan Baku Hasil Pertanian Lokal di Desa Pulau Semambu - Indah Solihah; Shaum Shiyan; Laida Neti Mulyani; Viva Starlista (Jurnal Pengabdian Pada Masyarakat, 2022)
PULAU SEMAMBU VILLAGE COVID 19 PREVENTION TRAINING ON LOCAL AGRICULTURAL HEALTH DRINK. The growing epidemic of COVID-19 poses a significant problem for the government and the population. Among the several measures used to avoid infection is the consumption of nutritious meals and beverages that boost the body’s immunity. Based on the results of the site survey; ginger, turmeric, lime, and pineapple are four antioxidant-rich plants that grow in Pulau Semambu Village. Turmeric contains curcumin, ginger contains shogaol and gingerol, and limes have high in vitamin C, those compounds play a vital function as an antioxidant and immunostimulant. Bromelain is an enzyme found in pineapple that can enhance the absorption of curcumin molecules. The activity was conducted utilizing lecture and live demonstration, discussion, and a pre- and post-test to assess participant knowledge. According to the hedonic test, syrup is considered acceptable. Based on the results of the test, it was found that participant’s knowledge had increased. The public knowledge of the COVID-19 transmission process has increased to 100%, 96% of respondents understand the causes of COVID-19, 96% of respondents understand the symptoms of COVID-19, and 92% of respondents understand how to prevent COVID-19. The community’s knowledge of herbal use also increased, 100% of respondents understand the sorts of herbs that can be used to prevent COVID-19, 72% of respondents understand how to process these herbs, and 92% of respondents understand how to prepare these herbs.